2019
DOI: 10.1111/resp.13681
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐observer variation in image interpretation and the prognostic importance of non‐expansile lung in malignant pleural effusion

Abstract: Background and objective Non‐expansile lung (NEL) frequently complicates management of malignant pleural effusion (MPE) and is an important factor in clinical practice and trials. NEL is frequently diagnosed on a single radiographic observation, but neither the inter‐observer agreement of this approach nor the prognostic importance of NEL in MPE has been reported. Methods A multicentre retrospective cohort study was performed in two UK pleural centres. NEL was defined as <50% pleural re‐apposition on post‐drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…How and where the patients are recruited may also influence the rates reported. Martin et al 2 found a two-fold difference in the incidence of NEL-34% (33/97) and 17% (15/86)between the two tertiary units. The study included only post-pleuroscopy patients, and the differences may, among other reasons, reflect differences in patient selection for the procedure.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…How and where the patients are recruited may also influence the rates reported. Martin et al 2 found a two-fold difference in the incidence of NEL-34% (33/97) and 17% (15/86)between the two tertiary units. The study included only post-pleuroscopy patients, and the differences may, among other reasons, reflect differences in patient selection for the procedure.…”
mentioning
confidence: 97%
“…How and where the patients are recruited may also influence the rates reported. Martin et al . found a two‐fold difference in the incidence of NEL— 34% (33/97) and 17% (15/86) — between the two tertiary units.…”
mentioning
confidence: 99%
See 3 more Smart Citations